Weed control in direct-seeded lowland rice under poor water control conditions - Akobundu, I.O. (Wiley, 1981)
Several herbicides applied singly and in combination were evaluated for weed control and for their effects on crop yield in direct‐seeded lowland rice under poor water management conditions characteristic of the conditions in which lowland rice is grown by most farmers in West Africa. Several herbicides including cyperquat at 3.0 kg/ha, a mixture of cyperquat and 2,4‐D at 2.0 + 0.5 kg/ha, bentazon at 2.0 kg/ha and avirosan satisfactorily controlled sedges in the 3‐year study. Crop yield was consistently high in plots where weeds were controlled with post‐emergence application of MCPA + propanil at 1.0+1.7 kg/ha, propanil + thiobencarb 2.2+1.2 kg/ha, oxadiazon 1.5 kg/ha, bentazon 2.0, granular 2,4‐D at 1.0 kg/ha, and a pre‐emergence application of bifenox at 2.0 kg/ha. Crop yields in plots treated with these herbicides were generally better than with two hand‐weedings.